A Sacral Mass in a Newborn: A Variant of Type II Diastematomyelia with Triple Splitting of the Cord - Emad Sadek Shatla; El Said M. A. Bedair; Ashraf Soliman (Case Reports in Pediatrics)
Ultrasonographic (US) evaluation of spinal anomalies is limited. MRI is increasingly being used in the diagnosis of spinal anomalies. MRI has been able to show clearly the detailed anatomy of this rare case of type II diastematomyelia with triple splitting of the cord.